Rheotaxis of Larval Zebrafish: Behavioral Study of a Multi-Sensory Process - Olive, Raphaël; Wolf, Sébastien; Dubreuil, Alexis; Bormuth, Volker; Debrégeas, Georges; Candelier, Raphaël (Frontiers in Systems Neuroscience, 2016)
Rheotaxis is the ability shared by most aquatic species to orient towards a current and swim to hold position. It is an innate and robust multi-sensory behavior that is known to involve the lateral line and visual systems. To facilitate the neuroethological study of rheotaxic behavior in larval zebrafish we developed an assay for freely swimming larvae that allows for high experimental throughput, large statistics and a detailed description of the behavior. We show that there exist a clear transition from exploration to counterflow swim, and by changing the sensory modalities accessible to the fishes (visual only, lateral line only or both) and comparing the swim patterns at different ages we characterized two different mechanisms for position holding, one mediated by the lateral line and one mediated by the visual system. We found that when both sensory modalities are accessible the lateral line dominates for triggering the transition while the visual system overshadows the lateral line for all aspect of swim patterns during the position holding phase. This suggests that at the larval stage the sensory inputs are not merged to finely tune the behavior but that one sensory modality dominates the behavioral response while redundant information pathways may be used as functional fallbacks.